1983
DOI: 10.1128/mcb.3.4.623
|View full text |Cite
|
Sign up to set email alerts
|

The structural genes for three Drosophila glue proteins reside at a single polytene chromosome puff locus.

Abstract: The polytene chromosome puff at 68C on the Drosophila melanogaster third chromosome is thought from genetic experiments to contain the structural gene for one of the secreted salivary gland glue polypeptides, sgs-3. Previous work has demonstrated that the DNA included in this puff contains sequences that are transcribed to give three different polyadenylated RNAs that are abundant in third-larval-instar salivary glands. These have been called the group II, group III, and group IV RNAs. In the experiments repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

1983
1983
2008
2008

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…The RNAs are all polyadenylated and polysomal (Meyerowitz and Hogness 1982). By comparing conceptual translations of the eDNA sequences with partial amino acid sequences of different glue polypeptides, it was found that each of the 68C RNAs codes for a different glue component (Crowley et al 1983). The 1120-nucleotide RNA is the mRNA for the sgs-3 glue polypeptide, which had previously been shown by genetic mapping to be coded in or near the 68C puff (Korge 1975;Akam et al 1978).…”
Section: Dna Sequence Organization Of the 68c Puffmentioning
confidence: 98%
See 1 more Smart Citation
“…The RNAs are all polyadenylated and polysomal (Meyerowitz and Hogness 1982). By comparing conceptual translations of the eDNA sequences with partial amino acid sequences of different glue polypeptides, it was found that each of the 68C RNAs codes for a different glue component (Crowley et al 1983). The 1120-nucleotide RNA is the mRNA for the sgs-3 glue polypeptide, which had previously been shown by genetic mapping to be coded in or near the 68C puff (Korge 1975;Akam et al 1978).…”
Section: Dna Sequence Organization Of the 68c Puffmentioning
confidence: 98%
“…Both genetic and molecular experiments have shown that these puffs contain the structural genes for the polypeptides that comprise the salivary gland glue (Korge 1975(Korge , 1977Akam et al 1978;Muskavitch and Hogness 1980;Velissariou andAshburner 1980, 1981;Crowley et al 1983;Gautam 1983;Guild and Shore 1984). This glue consists of at least eight polypeptides that start to be synthesized in the salivary glands in early to midthird instar, and stop synthesis at the time of puparium formation (Beckendorf and Kafatos 1976).…”
mentioning
confidence: 98%
“…stays nearly constant, The 68C puff of Drosophila melanogaster contains three genes that code for components of a protein glue that affixes the puparial case to a solid substrate (1)(2)(3). These genes are expressed abundantly in the salivary glands of third instar larvae and are controlled by the steroid hormone ecdysterone (4-7).…”
mentioning
confidence: 99%
“…As enzyme activity produced by fusion This observation is consistent with the kinds of fusion genes used. Sgs-7-Adh is a transcriptional fusion in the 5' untranslated leader of both genes and therefore produces native ADH protein that lacks a signal peptide for transport into the lumen (9). In contrast, Sgs-8-lacZ is a translational fusion with the coding sequences for 51 amino acids from Sgs-8 present and contains the signal peptide necessary for secretion into the lumen of the gland.…”
Section: Resultsmentioning
confidence: 99%